The Relationship Between Digital Literacy and Self-Perceived Academic Writing Ability Among EFL University Students - Angguni, Putri Elia; Saputri, Maulidarni; Sugesti, Nunik (Journal of Language and Literature Studies, 2026)
Digital literacy has become an essential competence in higher education, particularly for EFL (English as a Foreign Language) students who must not only develop linguistic proficiency but also effectively access, evaluate, and utilize digital academic resources to support academic writing. This study aimed to examine the relationship between digital literacy and self-perceived academic writing ability among master’s students in an English Language Education program at Yogyakarta State University. Employing a quantitative descriptive correlational design, the study involved 66 postgraduate EFL students as participants. Data were collected using a structured Likert-scale questionnaire measuring students’ digital literacy skills, including the use of academic databases, digital writing applications, and reference management tools, as well as their perceptions of academic writing ability in terms of idea organization, academic vocabulary, and writing coherence. The collected data were analyzed through descriptive statistics and Pearson correlation analysis. The findings revealed that students demonstrated high levels of digital literacy and self-perceived academic writing ability. Furthermore, the analysis showed a very strong and statistically significant positive correlation between digital literacy and academic writing ability (r = 0.985, p < 0.001). These results suggest that students with stronger digital literacy skills tend to perceive their academic writing competence more positively. The study underscores the importance of integrating digital literacy instruction into academic writing courses to enhance students’ writing confidence, learning autonomy, and overall academic performance in higher education contexts.